UJI AKTIVITAS ANTIBAKTERI FRAKSI EKSTRAK DAUN KERSEN (Muntingia calabura L.) TERHADAP BAKTERI Staphylococcus aureus - Brigita Aguilera Evarlin Jeharum; Iswandi; Destik Wulandari (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2025)
Staphylococcus aureus is a gram-positive bacterium that is part of the normal flora of human skin and mucous membranes. Staphylococcus aureus can cause infectious diseases. Cherry leaves are known to contain active compounds with antibacterial potential. The purpose of this study was to determine the antibacterial activity of cherry leaf extract fractions against Staphylococcus aureus bacteria, determine the MIC and MBC values, and detect the active fraction content. This study used an extraction method by maceration using 70% ethanol solvent and fractionation of cherry leaf extract using n-hexane, ethyl acetate, and water solvents. The disk diffusion method used a dilution series of 50%; 25%; 12.5% to obtain the most active fraction activity. The dilution method to determine the effectiveness of the concentration of the diffusion test with a dilution series of 50%; 25%; 12.5%; 6.25%; 3.12%; 1.56%; 0.78%; 0.39%. Data in the diffusion test were analyzed using SPSS to obtain the best activity. The normality test used the Shapiro Wilk test and homogeneity with Levene Statistic, then continued with the One Way ANOVA test. The results of the study showed that the most active extract fraction tested by the diffusion method was in the ethyl acetate fraction with a diameter of 26.95 mm. The ethyl acetate fraction tested by the dilution method had a MBC value of 6.25%. The ethyl acetate fraction was tested for content detection by Thin Layer Chromatography containing flavonoids, tannins, saponins, and alkaloids.